Experimental study on the collapse behavior of cavitation bubbles under low ambient pressure conditions - Tong Qu; Jing Luo; Weilin Xu; Jie Li; Guihua Fu; Yueqing Ma; Zhuoqi Zhao (Ultrasonics Sonochemistry)
Cavitation bubble dynamics at low ambient pressure differ from those at normal pressure, which can affect the efficiency of cavitation applications in industrial, medical fields, etc. Therefore, a low-voltage discharge method was utilized to produce cavitation bubbles in water at low ambient pressures (56 kPa to 96 kPa), and the impact of low ambient pressure on bubble collapse behavior was systematically studied. Experimental results show that as ambient pressure decreases, the pressure difference between the interior and exterior of bubbles, induced by identical energy, changes during their evolution. Consequently, the bubbles exhibit a gradual increase in maximum radius and an extended evolution period within an unbounded environment. Measurements of the shockwave intensity during bubble collapse revealed that under reduced ambient pressures, the peak pressure of shockwaves from bubble initial collapse gradually diminishes. Correspondingly, the proportion of shockwave energy relative to the bubble’s total mechanical energy also decreases progressively. Based on the behavior of bubbles under low ambient pressure conditions described above, it was found that as ambient pressure decreases, the maximum microjet velocity during cavitation bubble collapse in proximity to rigid walls gradually decreases at a constant bubble-wall distance. Furthermore, the peak of the maximum microjet velocity appears at approximately γ ≈ 0.8 across various ambient pressure conditions. These findings provide insights to enhance cavitation applications, including cavitation erosion prevention, medical treatments, and chemical catalysis in high-altitude and low-pressure environments.